That Fiduciary Relationship! - Nazli Hossain (Journal of the Pakistan Medical Association, 2025)
Mrs Z was received in the emergency room in a moribundstate. She was tachypnoeic, semi conscious, had multipletubings attached to her. She was accompanied by herdaughter, who appeared equally worried for her mother.Mrs Z had undergone a vaginal hysterectomy, aboutthree weeks ago at a centre which advertises itself ascentre for breast, hernia and obesity issues. She wasdischarged home next day after surgery from the hospital,only to return back the day after for abdominal pain anddiarrhoea. She was prescribed antibiotics and returnedhome by the surgeon. Soon these visits became frequentand the condition of Mrs Z deteriorated. She was unableto tolerate oral food, had fever and vomiting. The lack ofinterest on part of the primary surgeon resulted inattendant’s seeking a second opinion. She was againadmitted at a private tertiary care hospital but financialpressures brought them to a public sector hospital. Continued...